2011
DOI: 10.19030/jabr.v18i2.2118
|View full text |Cite
|
Sign up to set email alerts
|

Profit Margin And Capital Structure: An Empirical Relationship

Abstract: This study constitutes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 16 publications
9
38
0
9
Order By: Relevance
“…That is consistent with Eriotis et al (2011) [34] and (Strebulaev, 2007) [35]. Clearly, this result partially supports Hypothesis 4.…”
Section: Tests Of Hypotheses and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…That is consistent with Eriotis et al (2011) [34] and (Strebulaev, 2007) [35]. Clearly, this result partially supports Hypothesis 4.…”
Section: Tests Of Hypotheses and Discussionsupporting
confidence: 87%
“…[34] concluded that financing investment activities from internal sources was more profitable than sourcing borrowed capital. Even without consideration of the high costs of external financing, there should still be a negative relationship between profitability and the use of external financing [35].…”
Section: Hypothesismentioning
confidence: 99%
“…In Summary, the results shown on Tables (Table 10-15) indicate that capital structure, in general speaking has a negative and statistically significant influence on East African listed firm's financial performance at 5% significance level, which suggest that an increase in capital structure (STDR,LTDR and TDR) will result to a decrease in corporate financial performance (ROA and ROE).These results show that in average profitable listed firms in East African prefers to use internal source of financing in their capital structure as compared to external source of financing (like Debts-STDR,LTDR and TDR),the possible reasons for this situation is due several reasons such as Information asymmetry problems and financial markets in the East African region are still developing, hence it's difficult for profitable firms to access the external sources of financing (Like Corporate bonds), therefore decided to depend much on internal sources of financing (Like Bank borrowings) (Mwambuli,2015).Furthermore this results are supporting pecking order theory and our results are consistent with the findings of previous studies such as Kaumbuthu (2011), Karadeniz et al (2009), Zeitun & Tian (2007, Rao et al (2007), Huang & Sang (2006), Goddard et al (2005), Ngobo & Capiez (2004), Eriotis et al (2002), Fama & French (2002), Gleason et al (2000), Simerly & Li (2000), Majumdar & Chhibber (1999), Crnigol & Mramor (2009), Klapper & Tzioumis (2008), Dragota & Smenescu (2008), Song (2005), Chen (2004), Bauer (2004), Hall et al (2004), Deesomsak et al (2004), Cassar & Holmes (2003), Esperanca et al (2003), Nivorozhkin (2002), Shyam-Sunder & Myers (1999), Friend International Finance and Banking ISSN 2374-20892016, Vol. 3, No.…”
Section: Panels Corrected Standard Errors (Pcses) and Fixed Effect Resupporting
confidence: 91%
“…So, this manifests that debt affect profitability negatively; an increase in the debt ratio of 1% causes a decrease of corporate profitability by almost 0.15%. These findings support the results obtained by Majumdar and Chhibber (1999), Eriotis et al (2002), Ngobo and Capiez (2004), Goddard et al (2005), Rao et al (2007), Zeitun and Tian (2007) and Nunes et al (2009).…”
Section: Econometric Analysissupporting
confidence: 91%
“…A negative effect of debt on profitability was confirmed by Majumdar and Chhibber (1999), Eriotis et al (2002), Goddard et al (2005), Rao et al (2007), Zeitun and Tian (2007) and Nunes et al (2009). On the other hand, Baum et al (2006), Berger and Bonaccorsi (2006), Psillaki (2007, 2010), showed a positive influence.…”
Section: Introductionmentioning
confidence: 82%